High-Dose Glycine Treatment of Refractory Obsessive-Compulsive Disorder and Body Dysmorphic Disorder in a 5-Year Period - W. Louis Cleveland; Robert L. DeLaPaz; Rashid A. Fawwaz; Roger S. Challop (Neural Plasticity)
This paper describes an individual who was diagnosed with obsessive-compulsive disorder (OCD) and body dysmorphic disorder (BDD) at age 17 when education was discontinued. By age 19, he was housebound without social contacts except for parents. Adequate trials of three selective serotonin reuptake inhibitors, two with atypical neuroleptics, were ineffective. Major exacerbations following ear infections involving Group A 𝛽-hemolytic streptococcus at ages 19 and 20 led to intravenous immune globulin therapy, which was also ineffective. At age 22, another severe exacerbation followed antibiotic treatment for H. pylori. This led to a hypothesis that postulates deficient signal transduction by the N-methyl-D-aspartate receptor (NMDAR). Treatment with glycine, an NMDAR coagonist, over 5 years led to robust reduction of OCD/BDD signs and symptoms except for partial relapses during treatment cessation. Education and social life were resumed and evidence suggests improved cognition. Our findings motivate further study of glycine treatment of OCD and BDD.